A comprehensive analysis of satellite-induced code bias for BDS-3 satellites and signals. Issue 9 (1st May 2019) - Zhang, Xiaohong; Li, Xin; Lu, Cuixian; Wu, Mingkui; Pan, Lin
Abstract: Five BDS-3 satellites were launched successfully in 2015 and 2016, including two new-generation BDS-3 IGSO satellites I1-S and I2-S, and three new-generation BDS-3 Medium Earth Orbit (MEO) satellites M1-S, M2-S and M3-S. The BDS-3 satellites are able to transmit several new navigation frequencies including B1C at 1575.42 MHz, B2a at 1176.45 MHz, and B2b at 1207.14 MHz, in addition to B1 (1561.098 MHz) and B3 (1268.520 MHz) frequencies transmitted by BDS-2 satellites. Since the satellite-induced and elevation-dependent code biases were observed for the 14 older BDS-2 satellites (C01-C14), a comprehensive analysis and characterization of the code observations for the BDS-3 satellites were conducted based on observation data collected at 14 stations including 13 of the International GNSS Monitoring and Assessment System (IGMAS) and one station named SGG0 operated at the School of Geodesy and Geomatics (SGG) of Wuhan University. The Multipath (MP) combination, Melbourne-Wübbena (MW) combination and wide-lane uncalibrated phase delays (UPDs) are calculated to verify the existence and magnitude of the satellite-induced code bias for the BDS-3 satellites. The elevation-dependent polynomial models of MP combination for BDS-3 satellites were also established in order to analyze the characteristic of satellite-induced bias observed at different receiver types or different frequencies. For comparison, the MP combination of a newly launched BDS-2 satellite I6 was also calculated. The results indicate that the satellite-induced code bias is negligible for the BDS-3 satellites while newly launched BDS-2 satellite I6 has similar elevation-dependent code bias as the 14 older BDS-2 satellites.